Controlling Biological Activity with Light: Diarylethene‐Containing Cyclic Peptidomimetics1. (19th February 2014) - Babii, Oleg; Afonin, Sergii; Berditsch, Marina; Reiβer, Sabine; Mykhailiuk, Pavel K.; Kubyshkin, Vladimir S.; Steinbrecher, Thomas; Ulrich, Anne S.; Komarov, Igor V.
Abstract Photobiological processes in nature are usually triggered by nonpeptidic chromophores or by modified side chains. A system is presented in which the polypeptide backbone itself can be conformationally switched by light. An amino acid analogue was designed and synthesized based on a reversibly photoisomerizable diarylethene scaffold. This analogue was incorporated into the cyclic backbone of the antimicrobial peptide gramicidin S at several sites. The biological activity of the resulting peptidomimetics could then be effectively controlled by ultraviolet/visible light within strictly defined spatial and temporal limits.